Comas, Margarita (2001). Escritos sobre ciencia, género y educación. Edición de JoséMariano Bernal Martínez y Francesca Comas Rubí. Madrid: Biblioteca Nueva.Luzuriaga, Lorenzo (2001). La escuela única. Edición de Herminio Barreiro Rodríguez. - García Salmerón, María del Pilar (Revista Complutense de Educación, 2002)
Sin resumen